Sustainable Work Environmental Health Management Through the Evaluation of an Industrial Hygiene Program in the Nickel Mining Industry in North Konawe - Nurcitra Rehulina Br Ginting; I Made Astra; Dwi Atmanto; Eliana Sari; Ahman Sya; Nadiroh (Jurnal Green Growth dan Manajemen Lingkungan, 2026)
This study evaluated the implementation of the Industrial Hygiene Program in supporting sustainable work environmental health management in the nickel mining industry in North Konawe, Indonesia. The evaluation findings provide a basis for improving a more effective and sustainable Industrial Hygiene Program. This evaluation study employed the CIPPO (Context, Input, Process, Product, and Outcome) model using a mixed-methods approach. Data were collected through questionnaires and interviews involving 159 respondents selected by purposive sampling. The overall implementation of the program achieved a mean score of 3.23, indicating a moderate category. The context component showed an adequate program foundation, while the input, process, product, and outcome components require improvements in facilities, budget support, monitoring and evaluation, implementation of control recommendations to comply with Threshold Limit Values (TLVs), and enhancement of program benefits for workers and surrounding communities to support sustainable occupational environmental health management.